Formation of hydrophilic fibers containing polyhexamethylene biguanide and hyaluronic acid by electrospinning to wound healing - Lima, Lonetá Lauro (2024)
For good wound management, simultaneous phases during the wound healing process must be considered, including protection against infection, modulation of the inflammatory process, and proliferation and acceleration of cell migration. The aim of this study was to obtain Poly (Vinyl Pyrrolidone) (PVP) hydrophilic fibers containing polyhexamethylene biguanide (PHMB) and hyaluronic acid (HA) using the electrospinning technique to improve chronic wound treatment. Polymers mean hydrodynamic radius and polydispersity index (PdI) were measured by dynamic light scattering (DLS), whereas fiber morphology and diameter were evaluated by scanning electron microscopy (SEM). Also, Fourier transform infrared spectroscopy (FTIR) and contact angle measurements were performed. Fibers were obtained and presented homogenous morphology with a smooth surface. The FTIR study demonstrated an interaction between C=O groups of PVP and HA/PHMB in the PVP + HA/PHMB fibrous composites. Contact angle analysis has shown a hydrophilic characteristic of fibers produced. These findings demonstrate the great potential of electrospinning for developing drug-delivery systems with antimicrobial properties for wound healing treatment.